2016
DOI: 10.1007/s00380-016-0797-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of direct effects of clinically available vasodilators; nitroglycerin, nifedipine, cilnidipine and diltiazem, on human skeletonized internal mammary harvested with ultrasonic scalpel

Abstract: Direct vasodilator effects of nitroglycerin, nifedipine, cilnidipine and diltiazem on human skeletonized internal mammary artery graft harvested with ultrasonic scalpel were assessed in the presence of 0.1 or 0.2 µM of noradrenaline. Ring preparations were made of distal end section of the bypass grafts, and those dilated by acetylcholine were used for assessment. Each drug dilated the artery in a concentration-related manner (0.01-10 µM, n = 6 for each drug) with a potency of nitroglycerin > nifedipine = ciln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…An earlier RCT by Guadino et al suggested that long-term postoperative CCB was not associated with better RA graft patency and may not provide outcome bene ts for patients who had RA grafts 29,32 , although their recent study with questionable methodology argued against their previous conclusion: the post hoc analysis of data pooled from six RCTs comparing RA and SVG showed that chronic postoperative CCB therapy may improve RA graft patency and reduce the incidence of major cardiovascular events 33 . Numbers of in vitro and in vivo studies of RA sections or conduits indicated that nitroglycerin was more effective than diltiazem in preventing the contraction of RA grafts 30,34 ; compared to other CCBs, diltiazem was less effective in preventing graft contraction caused by endothelin-1 and norepinephrine, which affected RA more than LITA 28 . Chanda et al proposed that the combination of nitroglycerin and CCB may be more effective than a single agent for preventing RA graft spasm 31 .…”
Section: Discussionmentioning
confidence: 99%
“…An earlier RCT by Guadino et al suggested that long-term postoperative CCB was not associated with better RA graft patency and may not provide outcome bene ts for patients who had RA grafts 29,32 , although their recent study with questionable methodology argued against their previous conclusion: the post hoc analysis of data pooled from six RCTs comparing RA and SVG showed that chronic postoperative CCB therapy may improve RA graft patency and reduce the incidence of major cardiovascular events 33 . Numbers of in vitro and in vivo studies of RA sections or conduits indicated that nitroglycerin was more effective than diltiazem in preventing the contraction of RA grafts 30,34 ; compared to other CCBs, diltiazem was less effective in preventing graft contraction caused by endothelin-1 and norepinephrine, which affected RA more than LITA 28 . Chanda et al proposed that the combination of nitroglycerin and CCB may be more effective than a single agent for preventing RA graft spasm 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, data from recent studies investigating various categories of vasodilators show that the antispasmodic effects depend on the type of vessels and their specific mechanisms of graft spasm. 31 , 32 , 33 , 34 , 35 Taken together, the evidence suggests that instead of applying diltiazem to every patient, tailoring the antispasmodic interventions to the type and condition of the arterial grafts and the clinical condition of each individual patient may be more effective. A large-scale, multicentre retrospective outcome study may be warranted to better understand the effects of diltiazem on arterial grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Diltiazem is a calcium channel blocker which acts through L-type channel blockage [ 1 , 26 ] . It is another commonly applied vasodilator agent to prevent vasospasm and increase flow of coronary artery bypass conduits during CABG.…”
Section: Discussionmentioning
confidence: 99%